Reduced poly(ADP‐ribosyl)ation in lymphocytes of laryngeal cancer patients: Results of a case‐control study - Rajaee-Behbahani, Nahid; Schmezer, Peter; Ramroth, Heribert; Bartsch, Helmut; Becher, Heiko (International journal of cancer, 2002)
Poly(ADP‐ribose) polymerase (PARP), a nuclear enzyme that is catalytically activated by DNA strand breaks, plays a complex role in DNA repair. Using NAD+ as a precursor, it catalyzes the formation of ADP‐ribose polymers, which are attached to various proteins.